Disruption of Homeostasis Based on the Right and Left Hemisphere in Patients with Complex Regional Pain Syndrome - Jung, Ye-Ha; Kim, Hyeonjin; Lee, Dasom; Lee, Jae-Yeon; Lee, Won Joon; Moon, Jee Youn; Kim, Yong Chul; Choi, Soo-Hee; Kang, Do-Hyung (Neuroimmunomodulation, 2019)
Although the clinical features and pathophysiology of complex regional pain syndrome (CRPS) have been studied in the peripheral and central nervous systems, few plausible pathological interactions are known among the metabolites in these systems. Thus, the purpose of this study was to investigate abnormal relationships and interactions between peripheral metabolites and central neurometabolites in patients with CRPS. Various metabolites and molecules were measured in the peripheral blood, and central neurometabolites in the right and left thalamus using proton magnetic resonance spectroscopy in 12 patients with CRPS and 11 healthy controls. Interactions between peripheral metabolites in blood and central neurometabolites in the right and left thalamus were also investigated. The interactions between peripheral and central metabolites were different in the right and left hemispheres of healthy subjects, suggesting the presence of right hemisphere-dependent energy homeostasis and left hemisphere-dependent acid-base homeostasis that enables effective functioning. The interactions between central and peripheral metabolites in CRPS patients were distinct from those in healthy individuals, supporting the possibility of abnormal interactions and disrupted homeostasis between peripheral and central metabolites, which may result from neuroinflammation and immune system dysfunction. To the authors' knowledge, this is the first report describing abnormal metabolic dysfunction and disrupted homeostasis in interactions between metabolites of the peripheral and central nervous systems in CRPS. The approach used to uncover hidden pathophysiologies will improve understanding of how chronic pain can disrupt homeostasis in interactions between two systems and how alternative metabolites can be activated to recover and compensate for pathological dysfunctions in patients with CRPS.